Soil organic matter regression and degradation - Olga Kharaishvili; Ketevan Beriashvili; Tinatin Gogiashvili; Basa Zaalishvili; Tamaz Apakidze; Giorgi Winwarashvili (Reviews of Modern Science, 2024)
Georgia Since ancient times, it has been distinguished by its diversity, one of the components of which is the abundance of soils. Despite the territorial scarcity, 22 types of soils are widespread in the country, which are distinguished by such features as: mechanical composition, structure, humus content, cation exchange capacity, biodiversity, heat capacity and soil reaction. These differences are determined by abiotic factors: heat, light, humidity, relief; they participate not only in creating a living environment for plants, but also affect the fertility of agricultural lands. As a result of the high humidity in Western Georgia, red soil and yellow soil soils are mainly found. In addition to the content of organic matter, the formation of color is determined by the degree of oxidation, the course of which depends on the chemical elements present in the soil. A high degree of oxidation determines dark coloring, and a low one - light. At the same time, in the western zone, there are widespread chernozem soils, which are not used in agriculture due to the low content of nutrients.